A Comparative Study of Magnetic Properties of Large Diameter Co Nanowires and Nanotubes - Jose Angel Fernandez-Roldan; Dieivase Chrischon; Lucio Strazzabosco Dorneles; Oksana Chubykalo-Fesenko; Manuel Vazquez; Cristina Bran (Nanomaterials, 2018)
A comparative study of the magnetic properties of the arrays of Co nanowires and nanotubes with large external diameters (180 nm) has been carried out. The nanowires/nanotubes were grown by electrodeposition into the self-assembled pores of anodic alumina membranes. The experimental study of their magnetic behavior was focused on the angular dependence of hysteresis loops and their parameters. In both nanowire and nanotube arrays, from the analysis of experimental data, effective longitudinal magnetic anisotropy is concluded, which is stronger in the case of the nanotube array. In addition, the extremely small remanence observed for all loops indicates the important role played by magnetostatic interactions. Micromagnetic simulations were first performed considering intrinsic shape and magnetocrystalline anisotropy terms, together with an effective easy-plane anisotropy to account for those magnetostatic interactions. A qualitative agreement between experiments and simulations is found despite the complexity introduced by the intrinsic and extrinsic array properties (i.e., large diameters, grain structure, and array configuration). In addition, simulations were also carried out for individual nanowire/nanotube with a particular emphasis to understand their differences at the remanence, due to pure geometry contribution.